Ambient Zinc K-Edge Extended X-Ray Absorption Fine Structure Studies on Solid Solution Hardening of the Zn1−xBexSe Ternary Alloys. (10th January 2013) - Khan, Shabina; Mazher, Javed; Singh, Pankaja
Abstract : Solid solution hardening can be introduced in the zinc selenide by cationic substitution alloying. We are presenting our studies on gradual development of the hardening and the bond-length variations among the heavily Be-doped ternary alloys of Zn 1 − x Be x Se . These compositionally vivid ternary systems are grown by the Bridgman technique, and a set of careful measurements of synchrotron-based Zn core X-ray absorption spectroscopy are performed on the mixed alloy, which is followed by extraction of useful oscillations of extended X-ray absorption fine structures. A detailed ab initio analysis is also carried out for the mixed alloy's theoretical EXAFS simulations, and suitable data processing codes are used for the subsequent experimental spectra fittings. Various X-ray scattering single and multiple paths around the core atomic environ are simulated and compared with the spectroscopic results. With the aid of as-found parametric values, the hardening and crystalline disorders are discussed and explained in the midst of the multimodal bond-length behaviors and changes induced by the increased alloying amid as-found pseudocrystalline stabilities.